Heuristic Barycenter Modeling of Fully Absorbing Receivers in Diffusive Molecular Communication Channels - Vakilipoor Takaloo, Fardad; N.M. Ansari, Abdulhamid; Magarini, Maurizio (IEEE Transactions on Communications, 2024)
In a recent paper it has been shown that to model a diffusive molecular communication (MC) channel with multiple fully absorbing (FA) receivers, these can be interpreted as sources of negative particles from the other receivers' perspective. The barycenter point is introduced as the best position where to place the negative sources. The barycenter is obtained from the spatial mean of the molecules impinging on the surface of each FA receiver. This paper derives an expression that captures the position of the barycenter in a diffusive MC channel with multiple FA receivers. In this work, a heuristic model inspired by Newton's law of gravitation is found to describe the barycenter, and the result is compared with particle-based simulation (PBS) data. Since the barycenter depends on the distance between the transmitter and receiver and the observation time, the condition that the barycenter can be assumed to be at the center of the receiver is discussed. This assumption simplifies further modeling of any diffusive MC system containing multiple FA receivers. The resulting position of the barycenter is used in channel models to calculate the cumulative number of absorbed molecules and it has been verified with PBS.
Created from Fastlane, Scopus look-up
Keywords: channel models; diffusion processes; Molecular communication; receivers; SIMO communication